Kredibilitas Content Micro Influencer dan Dampaknya pada Purchase Intention: Peran Digital Engagement UMKM Kuliner - Saharuddin Saharuddin; Hasrullah Liong Misi; Andi Irsandi Yusri (Forum Kerjasama Pendidikan Tinggi, 2026)
One increasingly relevant approach is the use of micro-influencers, whose content credibility is believed to foster consumer trust and encourage digital engagement. However, many MSME actors still face challenges in optimizing influencer marketing, and prior research has reported contradictory findings. This study aims to analyze the effect of micro-influencer content credibility on consumers’ purchase intention in culinary MSMEs, both directly and indirectly through brand trust and digital engagement. A quantitative approach was employed using Structural Equation Modeling (SEM) with the assistance of AMOS software. Data were collected from 210 respondents who are consumers of culinary MSMEs in Pare-Pare City and Pinrang Regency, South Sulawesi, Indonesia. The results show that micro-influencer content credibility has a significant positive effect on brand trust, digital engagement, and purchase intention. Furthermore, digital engagement was found to mediate the relationship between micro-influencer content credibility and purchase intention, while the mediating role of brand trust was not significant. These findings provide theoretical contributions to the literature on influencer-based digital marketing and practical implications in the form of recommendations for MSMEs to optimize collaborations with credible micro-influencers in creating interactive content that enhances consumer digital engagement and drives purchase intention.